Analysis and Design of a Web-Based Marketing Information System with a CRM (Customer Relationship Management) Approach at Tenun Resti Sipirok - Ofelius Laia; Jurisman Waruwu; Arisman Telaumbanua (Institute of Computer Science (IOCS), 2023)
Tenun Resti Sipirok is a company engaged in trading woven products such as Jas, Ulos, Souvenirs and other woven products. In marketing its products, Tenun Resti Sipirok still uses the shop as a marketing place, so that consumers who are interested in buying these products must come directly to the store where they are marketed. Not infrequently consumers are disappointed because the product they want to buy is not available which requires consumers to order in advance until the product is finished being produced. By designing and implementing a web-based marketing system with a CRM approach to Tenun Resti Sipirok, it is very helpful in the process of marketing products via the internet, such as selling and promoting products to consumers. This also has a positive impact on the consumer side, because consumers do not have to come directly to the marketing shop, but consumers can buy and order products through the website that is created and information about new products and promos is easy for consumers to get through the website page as well as via email messages.